2015
DOI: 10.1093/mnras/stv2722
|View full text |Cite
|
Sign up to set email alerts
|

Mergers and the outside-in formation of dwarf spheroidals

Abstract: We use a cosmological simulation of the formation of the Local Group to explore the origin of age and metallicity gradients in dwarf spheroidal galaxies. We find that a number of simulated dwarfs form "outside-in", with an old, metal-poor population that surrounds a younger, more concentrated metal-rich component, reminiscent of dwarf spheroidals like Sculptor or Sextans. We focus on a few examples where stars form in two populations distinct in age in order to elucidate the origin of these gradients. The spat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 59 publications
6
68
1
Order By: Relevance
“…These results have also been reproduced by simulations (e.g. Schroyen et al 2013;Revaz & Jablonka 2018), which have shown that the shape of these gradients strongly depends on the combination of the stellar mass, SFH and dynamical history of the system under consideration, although their strength could be influenced by merger events (Benítez-Llambay et al 2016) or environmental effects such as tidal stripping (Sales et al 2010).…”
Section: Metallicity Propertiessupporting
confidence: 62%
“…These results have also been reproduced by simulations (e.g. Schroyen et al 2013;Revaz & Jablonka 2018), which have shown that the shape of these gradients strongly depends on the combination of the stellar mass, SFH and dynamical history of the system under consideration, although their strength could be influenced by merger events (Benítez-Llambay et al 2016) or environmental effects such as tidal stripping (Sales et al 2010).…”
Section: Metallicity Propertiessupporting
confidence: 62%
“…Some of these differences could indicate an ancient merger, which would have dispersed the old stellar component and allowed the enriched gas to sink further in before forming stars (Benítez-Llambay et al 2016;Genina et al 2019). This would provide a plausible explanation for the radial offset between the original distribution of Fornax GCs and the present-day distributions of its stars.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, direct observational evidence for mergers between dwarf galaxies has been discovered (e.g., Martínez-Delgado et al 2012;Penny et al 2012;Rich et al 2012;Johnson 2013;Nidever et al 2013;Crnojević et al 2014;Paudel et al 2015;Stierwalt et al 2015). Furthermore, for the first time, the latest numerical simulations are able to reach the required resolution in order to study the effects of dwarf-dwarf mergers in a cosmological scenario (Klimentowski et al 2010;Kazantzidis et al 2011;Deason et al 2014;Benítez-Llambay et al 2016), and these demonstrate that dwarf-dwarf mergers are a viable mechanism to form dwarf spheroidals in the Local Group environment (Kazantzidis et al 2011).…”
Section: Introductionmentioning
confidence: 95%